2019
DOI: 10.1021/acs.chemrev.9b00316
|View full text |Cite
|
Sign up to set email alerts
|

UV Photoinduced Dynamics of Conformer-Resolved Aromatic Peptides

Abstract: A detailed understanding of radiative and nonradiative processes in peptides containing an aromatic chromophore requires the knowledge of the nature and energy level of low-lying excited states that could be coupled to the bright 1 * excited state. Isolated aromatic amino acids and short peptides provide benchmark cases to study, at the molecular level, the photoinduced processes that govern their excited state dynamics. Recent advances in gas phase laser spectroscopy of conformer-selected peptides have pave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 319 publications
(603 reference statements)
0
70
0
Order By: Relevance
“…The last fragmentation channel at m/z 32 is assigned to the NH3CH3 + ionic fragment (C-N bond break). It should be stressed here that such fragmentation pattern, competition between CID like fragments and specific UV fragments issued from the C-C bond break, 10 is commonly observed in the UV photodissociation of protonated aromatic amines, 27 amino acids, 28-31 catecholamine 7 and short peptides. [32][33][34][35][36][37] As it can be readily seen in Fig.…”
Section: Conformer Assignment: Uv Photodissociation and Uv-uv Holementioning
confidence: 82%
See 2 more Smart Citations
“…The last fragmentation channel at m/z 32 is assigned to the NH3CH3 + ionic fragment (C-N bond break). It should be stressed here that such fragmentation pattern, competition between CID like fragments and specific UV fragments issued from the C-C bond break, 10 is commonly observed in the UV photodissociation of protonated aromatic amines, 27 amino acids, 28-31 catecholamine 7 and short peptides. [32][33][34][35][36][37] As it can be readily seen in Fig.…”
Section: Conformer Assignment: Uv Photodissociation and Uv-uv Holementioning
confidence: 82%
“…Such photoinduced reaction has previously been assigned in aromatic amines, amino acids and related systems such as synephrine to excited state proton transfer from the ammonium group to the aromatic ring. 10 In the optimized structure of the * state of conformer A, a lengthening of the N-H bond (0.023 Å) pointing to the ring along with an out-of-plane bending of the CH (≈30°) facing the protonated group are observed (see Fig. S8).…”
Section: Articlementioning
confidence: 98%
See 1 more Smart Citation
“…[7] In a nutshell, it has been suggested that the nature of coupling (or lack of it) of the initially excited 1 ππ* bright state to one or more low-lying excited states largely determines the nature of excited state dynamics. [8] In the case of the binary complex of phenylacetylene with methylamine, it was earlier reported, that the emissive nature of the initially excited 1 ππ* (S 1 ) state was dependent on the intermolecular structure, wherein the formation of � CÀ H•••N complex leads to fluorescence quenching while the NÀ H•••π complex was fluorescent. [9] The electron transfer mechanism of fluorescence quenching by amines is well known, at least in the condensed phases.…”
Section: Introductionmentioning
confidence: 99%
“…Conformer-selective UV spectra may be recorded by using UV/UV double resonance techniques, 10 but conformer-selection can also be achieved using ion mobility. 11 Otherwise, UV chromophores take a critical part in the conformer-selection process for other types of spectroscopy, like conformer-selective IR 12–14 or photoinduced dynamics, 15 and in the measurement of the fractional abundances of a conformational mixture, 16 which can be considered as the ultimate goal of conformational analysis.…”
Section: Introductionmentioning
confidence: 99%